2005
DOI: 10.1103/physrevlett.95.245501
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Fragile Metallic Glasses Inferred from Ultrasound-Accelerated Crystallization in Pd-Based Metallic Glasses

Abstract: By utilizing ultrasonic annealing at a temperature below (or near) the glass transition temperature Tg, we revealed a microstructural pattern of a partially crystallized Pd-based metallic glass with a high-resolution electron microscopy. On the basis of the observed microstructure, we inferred a plausible microstructural model of fragile metallic glasses composed of strongly bonded regions surrounded by weakly bonded regions (WBRs). The crystallization in WBRs at such a low temperature under the ultrasonic vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
157
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(169 citation statements)
references
References 31 publications
11
157
0
1
Order By: Relevance
“…42 Nevertheless, according to elastic models of glass forming, the barrier transition for a "flow event" ͑an atomic rearrangement͒ does take place on a very short time scale. 43 Furthermore, both Egami's atomistic theory 8 and the microstructural model of Ichitsubo et al 6 can perfectly explain the Novikov-Sokolov observations. Actually, in their models, the temperature-dependent modulus was neglected, which corresponds to b͑T ; m , G͒ϵ0 in our case.…”
Section: A Fragility and Bulk-shear Modulus Ratiomentioning
confidence: 52%
See 1 more Smart Citation
“…42 Nevertheless, according to elastic models of glass forming, the barrier transition for a "flow event" ͑an atomic rearrangement͒ does take place on a very short time scale. 43 Furthermore, both Egami's atomistic theory 8 and the microstructural model of Ichitsubo et al 6 can perfectly explain the Novikov-Sokolov observations. Actually, in their models, the temperature-dependent modulus was neglected, which corresponds to b͑T ; m , G͒ϵ0 in our case.…”
Section: A Fragility and Bulk-shear Modulus Ratiomentioning
confidence: 52%
“…5 Due to the technological and the scientific significance of this surprising finding, it has attracted a lot of discussions. [6][7][8][9][10] However, the question whether such a linear correlation universally exists still remains open up to now. As for metallic glasses, a number of important correlations among their properties have been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the interpretation of the NMR measurements 31,32 in terms of small-angle motions of all molecules would not be applicable to all types of glasses. Furthermore, a recent paper by Ichitsubo et al 59 has described a microstructural model for a glass consisting of a mixture of weakly regions ͑islands of mobility͒ and stronglybonded regions.…”
Section: Molecular Aspects Of the Change In Jg-relaxation Featuresmentioning
confidence: 99%
“…In addition to the primary (a-) relaxations that are responsible for the viscous flow, a kind of secondary relaxation, called Johari-Goldstein or b-relaxation [7][8][9] , often exists at high frequencies or low temperatures. Recent studies have demonstrated that b-relaxations are an intrinsic and universal feature of supercooled liquids and glasses 1,8,10 , and they are of significance to the understanding of many key issues in glassy physics and material sciences 1 , ranging from glass transition phenomenon [10][11][12][13] , diffusions [14][15][16][17] , physical aging 18,19 to mechanical properties 20,21 and mechanisms of plastic deformations [21][22][23] , as well as the stabilities and crystallization of glassy materials [24][25][26] .…”
mentioning
confidence: 99%